SLE: a cognitive step forward—a synthesis of rethinking theories, causality, and ignored DNA structures - Rekvig, Ole Petter (Frontiers in Immunology, 2024)
Systemic lupus erythematosus (SLE) is classified by instinctual classification criteria. A valid proclamation is that these formally accepted SLE classification criteria legitimate the syndrome as being difficult to explain and therefore enigmatic. SLE involves scientific problems linked to etiological factors and criteria. Our insufficient understanding of the clinical condition uniformly denoted SLE depends on the still open question of whether SLE is, according to classification criteria, a well-defined one disease entity or represents a variety of overlapping indistinct syndromes. Without rational hypotheses, these problems harm clear definition(s) of the syndrome. Why SLE is not anchored in logic, consequent, downstream interdependent and interactive inflammatory networks may rely on ignored predictive causality principles. Authoritative classification criteria do not reflect consequent causality criteria and do not unify characterization principles such as diagnostic criteria. We need now to reconcile legendary scientific achievements to concretize the delimitation of what SLE really is. Not all classified SLE syndromes are “genuine SLE”; many are theoretically “SLE-like non-SLE” syndromes. In this study, progressive theories imply imperative challenges to reconsider the fundamental impact of “the causality principle”. This may offer us logic classification and diagnostic criteria aimed at identifying concise SLE syndromes as research objects. Can a systems science approach solve this problem?